Мужская исповедь: стихи / Н. Е. Баженов - Баженов Николай Евгеньевич (Удмуртия, 2015)
Экземпляры: ЦБ (20161116) / Инвентарный номер: 53119 / Цена: 50.00 / Сис.шифр: Р2 / Авт.знак: Б 16 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6